Causes of stress and management approaches among undergraduate pharmacy students: Findings from a Malaysian public university - Jamshed, Shazia Qasim; James, Peter B.; Elkalmi, Ramadan Mohamed Mahmod; Mohammed Ahmed, Abdul Kareem; Nor, Ashraf; Kabir, Fauzal; Sumali, Izzurean; Zubair, Ahmad; Shamsudin, Siti Hadijah (Wolters Kluwer - Medknow, 2017)
Background: Stress is one of the psychological problems that affect one’s mental and physical condition. In today’s era, students seem to be in stress continuously, which affects their academic performance as well as participation in non-academic activities. The aims of the current research are to explore the different causes of stress among pharmacy students and identify the different ways of management of stress. Materials and Methods: This is a cross-sectional study design, in which all the undergraduate pharmacy students of International Islamic University Malaysia, registered in semester 1, 2013/2014 were recruited. A total of 300 students from 1st professional to 4th professional participated in the study. The survey instrument was designed based on previously published research and subjected to face validity and content validity. Cronbach alpha computed and found to be 0.68. Data analyzed using International Business Machine Statistical Package for the Social Sciences Statistic version 21 (IBM SPSS Inc., Chicago, IL, USA), and descriptive and inferential statistics applied. Results: In the current research, majority of students (n= 258; 89%) reported quizzes as the leading cause of stress. We observed a significant correlation between age range (P=0.009) and year of study (P=0.006) to quizzes. On the contrary, inadequate support from teachers stated as the minimal cause of stress (n=22; 7.3%). Most of the respondents agreed (210 students; 70%) that sleeping is the best way to relief stress. Conclusion: Keeping in view the competitive environment among students, the management of stress cannot be sidelined. Counseling programs can be instituted in each semester, which is expected to inculcate stress managementing approaches in daily life activities of students.